Chronic Hemodialysis Patients Without Marked Elevation of Intact Parathyroid Hormone Are Also Good Candidates for Early Intervention With Cinacalcet. Issue 3 (22nd January 2013) - Nishida, Hayato; Masakane, Ikuto; Kudo, Kenichi; Ito, Minoru; Tanida, Hideki; Koshika, Masataka; Nishida, Wakako; Tomita, Yoshihiko
Abstract Management of calcium (Ca) and phosphorus (P) metabolism is crucial in chronic hemodialysis (HD) patients. Cinacalcet is usually used for chronic kidney disease‐mineral and bone disorders (CKD‐MBD) patients with elevated intact parathyroid hormone (iPTH) levels. However, a certain number of CKD‐MBD patients have normal iPTH levels and are not subjected to cinacalcet therapy. Here, we evaluated the efficacy of a new treatment algorithm of early initiation of cinacalcet therapy in this subgroup of patients, mainly for correcting Ca and P metabolism. Seventy‐one HD patients, including 44 patients without marked elevation of iPTH (102 < iPTH ≤ 300 pg/mL), who received cinacalcet therapy, were enrolled in this study. Serum parameters relating to CKD‐MBD patient metabolism, doses of phosphate binders, and type of vitamin D sterols were compared between pre‐ and post‐cinacalcet administration retrospectively. Sixty‐four of 71 patients did not require discontinuation of cinacalcet. In these 64 patients, serum Ca (P = 0.0003), P (P = 0.0153), and iPTH (P < 0.0001) levels were significantly reduced after cinacalcet administration, even in those without marked elevation of iPTH (Ca; P < 0.0001, P; P = 0.0422, and iPTH; P = 0.0018). The proportion of patients who received vitamin D sterols was unchanged (P = 0.5930) but the proportion of patients who received maxacalcitol was significantly reduced after cinacalcet administration (P = 0.0108). The new treatment algorithm of early initiation of cinacalcet is considered to be well tolerated and effective for controlling hypercalcemia, and/or hyperphosphatemia and/or increased iPTH of CKD‐MBD patients.